Seven‐year trends in sun protection and sunburn among Australian adolescents and adults - Angela Volkov; Suzanne Dobbinson; Melanie Wakefield; Terry Slevin (Elsevier, 2013)
Abstract Aims : To examine the change in sun protective behaviours and sunburn of Australians over a seven‐year period, in the context of sustained skin cancer prevention campaigns and programs. Methods : Weekly cross‐sectional telephone interviews of Australians were conducted throughout summer in 2010/11 for comparison with 2003/04 and 2006/07. In 2010/11, n=1,367 adolescents (12-17 years) and n=5,412 adults (18-69 years) were interviewed about their sun‐related attitudes, weekend sun protection and sunburn. Multivariate analyses adjusted for key demographics, temperature, cloud, wind and ultraviolet radiation (UVR) to assess change in outcomes over time. Results : There were consistent improvements in adolescents' and adults' attitudes, intentional tanning and incidence of sunburn over time. Behavioural changes were variable. Adults spent less time outdoors during peak UVR compared to past surveys, while adolescents were less likely to be outdoors compared with 2006/07. Sunscreen use and wearing of long sleeves increased among adults, but hat wearing decreased for both age groups, as did leg cover by adolescents since 2003/04. There has been a sustained decrease in weekend sunburn among adolescents and adults. Conclusions : The findings suggest improvements in skin cancer prevention attitudes of Australians over time. Australians' compliance with sun protection during summer has improved in some areas, but is still far from ideal. The sustained decrease in weekend sunburn among adolescents and adults is encouraging, but further improvements are required.